A comparative study of the metal candlestick images in the paintings of Shahnameh of Shah Tahmasb and similar examples of Islamic periods (Seljuk, Ilkhanid, Timurid and Safavid periods) - Sahar Zekavat (پیکره, 2020)
Problem definition: Metal candlestick is one of the most widely used accessory for providing lighting and one of the common tools of the past periods whose images are abundantly depicted in the Shahnameh’s paintings and the display of these objects has always been of interest to the artists. The present study aims to investigate the general characteristics of the candlestick images in the paintings of Shahnameh of Shah Tahmasb and explore the commonalities and differences between these images and examples of handmade and metal candlesticks of the Islamic period, especially in the "Seljuk", "Ilkhanid", "Timurid" and "Safavid" periods. The present study will finally answer the question that the candlestick image in the paintings of Shahnameh of Shah Tahmasb is more similar to the handmade works of which of the studied periods. Objective: To identify the style and context of objects and elements of Iranian paintings in order to perceive the mental influences of ancient Iranian artists in their lifetime Research Method: The research data has been collected in the library-documentary form and investigated using descriptive-analytical method and a comparative approach. The present samples were taken using purposive sampling method and from 18 types of candlesticks associated with different periods of the Iranian government, 2 have been selected from the Seljuk, 10 from Ilkhanid and Timurid and 6 from Safavid periods. Also, the statistical population of the examined paintings includes 174 drawings in the Shahnameh of Shah Tahmasb, published by the Academy of Arts, of which the images of 4 candlesticks have been identified in 4 ones. Results: The results indicated that the candlestick samples of the Shahnameh paintings do not resemble the metal handmade ones belonging to the Safavid period and there are many differences between the images and samples of this period. The candlestick samples of Safavid period are cylindrical, but other ones have a polygonal base. The general characteristics of these candlesticks are more similar to the hand-made ones belonging to the Seljuk, Ilkhanid and Timurid periods.